Julia Kristeva and feminist thought - Schippers, Birgit (Edinburgh : Edinburgh University Press, 2011)
This book appraises the relationship between contemporary feminism and Julia Kristeva, a major figure in Continental thought. It addresses the conflicting range of feminist responses to Kristeva's key ideas and Kristeva's equally conflicting as well as ambiguous position vis-Ã€-vis feminism. Schippers argues that this complex relationship can only be understood by positioning Kristeva along the fissures and fault lines which run through feminism. By attending to feminism's internal debates and disputes, and addressing the philosophical commitments and attachments held by Kristeva's critics, the book clarifies the diverse Kristeva reception within feminism and illuminates how her ideas trouble contemporary feminist thought. And despite Kristeva's fundamental ambiguity towards all matters feminist, Schippers makes a case for Kristeva's important contribution to a feminist project which is sympathetic towards her account of fluid subjectivity and her critique of identity politics. In doing so, the author advances the scholarly understanding of Kristeva and of contemporary feminist thought.
Introduction -- 1. Kristeva and feminism : a critical encounter -- 2. Crisis, revolt, intimacy -- 3. Corporeal ethics : between violence and forgiveness -- 4. The singularity of genius -- 5. Towards a philosophy of freedom?
Includes bibliographical references (pages 175-191) and index.
Print version record.
eBooks on EBSCOhost
Keywords: Kristeva, Julia, -- 1941- -- Criticism and interpretation; Kristeva, Julia, -- 1941-; Kristeva, Julia; Feminism in literature; Feminism; Feminism; Féminisme dans la littérature.; Féminisme.; feminism; SOCIAL SCIENCE -- Feminism & Feminist Theory; PHILOSOPHY -- General; Feminism; Feminism in literature; Feminismus; Electronic books; Criticism, interpretation, etc